Interpersonal verbal conflict in Ukrainian environment (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article presents the results of the survey. It was found that respondents’ perception of ethno-cultural, cognitive and pragmatic nature of interpersonal verbal conflict actualized because of their “conflict experience”. This knowledge was the basis for determining the significance of the conflict, to interpret the tactics of communicative actions of individuals. The respondents believe that the success of the interaction is governed by speech “laws” that are part of the moral and ethical norms of society.
Keywords: interpersonal verbal conflict; conflictogen; speech tactics; cognitive and pragmatic factors; moral and ethical standards